Lithium antagonizes dopamine-dependent behaviors mediated by an AKT/glycogen synthase kinase 3 signaling cascade - Beaulieu, Jean-Martin (National Academy of Sciences, 2004)
Dopamine (DA) is a neurotransmitter involved in the control of locomotion, emotion, cognition, and reward. Administration of lithium salts is known to inhibit DA-associated behaviors in experimental animal models through unknown mechanisms. Here, we used a pharmacogenetic approach to show that DA can exert its behavioral effects by acting on a lithium-sensitive signaling cascade involving Akt/PKB and glycogen synthase kinase 3 (GSK-3). In the mouse striatum, increased DA neurotransmission arising either from administration of amphetamine or from the lack of the DA transporter results in inactivation of Akt and concomitant activation of GSK-3α and GSK-3β. These biochemical changes are not affected by activation of the cAMP pathway but are effectively reversed either by inhibition of DA synthesis, D2 receptor blockade, or administration of lithium salts. Furthermore, pharmacological or genetic inhibition of GSK-3 significantly reduces DA-dependent locomotor behaviors. These data support the involvement of GSK-3 as an important mediator of DA and lithium action in vivo and suggest that modulation of the Akt/GSK-3 pathway might be relevant to DA-related disorders, such as attention deficit hyperactivity disorder and schizophrenia.